Test-retest validity and reliability of the MA related Go/No-Go task in assessing inhibitory control and attentional bias in methamphetamine users. - Namvar, GholamReza; Ebrahimi-Kalan, Abbas; Shafiee Kandjani, Ali Reza; Ghadiri, Tahereh; Jahan, Ali; Samadishadlou, Mehrdad; Moghadam Salimi, Maryam (Journal of Substance Use, 2026)
Objective: Methamphetamine (MA) addiction is associated with significant cognitive impairments, particularly in attentional bias and inhibitory control. These deficits complicate recovery and increase the likelihood of relapsing. This study aims to evaluate the test-retest validity and reliability of a modified Go/No-Go task designed to measure these cognitive deficits in MA-dependent individuals. Methods: Forty MA-dependent individuals and fifty healthy controls participated in a two-session experiment. Both groups completed a MA-related Go/No-Go task, comprising blocks of neutral, negative, and MA-related cues. Efficiency Scores (ES) were calculated based on omission and commission errors, normalized by reaction time. Test-retest reliability was assessed through Pearson correlation coefficients, and differences between groups were analyzed using independent and paired t-tests. Results: Significant differences in ES were observed between MA-dependent individuals and controls for MA-related and neutral cues, but not for negative cues. Strong correlations in test-retest ES were noted in both groups, particularly for MA-related cues in MA addicts. However, the task showed limited sensitivity in distinguishing between cue types within the addicted group. Conclusion: The MA related Go/No-Go task shows moderate to strong test-retest reliability but limited sensitivity in distinguishing cognitive responses across cue types in MA addicts.